Cyberbullying among college students in a Chinese population: Prevalence and associated clinical correlates - Jin, Xingyue; Zhang, Kun; Twayigira, Mireille; Gao, Xueping; Xu, Huiming; Huang, Chunxiang; Luo, Xuerong; Shen, Yanmei (Frontiers in Public Health, 2023)
Objectives Cyberbullying is quite common in adolescents and college students, and it influences mental health in many aspects. The purpose of this study was to investigate the prevalence of cyberbullying in Chinese college students and to look for related factors. Methods Eight thousand and ninety-eight college students aged 17–26 were enrolled in this cross-sectional study. We collected information of their sociodemographic data, depression (evaluated by Self-Rating Depression Scale), anxiety (evaluated by Self-Rating Anxiety Scale), lifetime suicidal behaviors (including suicidal ideation, suicidal plans, and suicide attempts), and experiences of cyberbullying for the past 12 months by online questionnaires. Results The prevalence of cyberbullying for the past 12 months was 7.82% (633/8,098) among college students. Binary logistic regression analysis showed that sex (odds ratio, OR = 0.522, 95%CI = 0.433–0.629, p < 0.001), suicide attempts (OR = 2.164, 95%CI = 1.589–2.948, p < 0.001), depression (OR = 2.372, 95%CI = 1.602–3.512, p < 0.001), and anxiety (OR = 1.911, 95%CI = 1.305–2.800, p = 0.001) were independently associated with cyberbullying. Conclusion Cyberbullying is very common among college students in Hunan Province, China. Besides, being male, suicide attempts, depression and anxiety were independently associated with cyberbullying, which highlights the importance of paying attention to cyberbullying and addressing anxiety, depression, and suicidal behaviors among college students to better improve their mental health and prevent suicide.